Chondroblastoma of the talus: a case report - Barbosa, Thiago Moreth da Silva; Souza, Antonio Marcelo Gonçalves de; Alves, João Victor de Lima Brito; Moreth, Micaella dos Santos Andrade; Vieira, Kellem Carol Muniz; Freire, Vitor Benedito Ferreira (Journal of the Foot & Ankle, 2023)
Chondroblastoma is a rare benign cartilaginous tumor comprising approximately 1% of all bone tumors. It usually occurs in patients from 10 to 25 years, being more frequent in men (2:1). It is usually located in the epiphysis of long bones, mainly in the distal femur, tibia, and proximal humerus, in individuals with open physis. This paper presents an atypical presentation of chondroblastoma of the talus, with few similar publications in the literature. A 33-year-old male patient was treated in a hospital with pain in his left ankle for about three years. After imaging and histopathological examinations, the hypothesis of chondroblastoma was confirmed, and resection with intralesional margin was performed. Level of Evidence V; Case Report; Expert Opinion.